Pelaksanaan Pengawasan dan Penegakan Hukum Izin Usaha Toko Swalayan Oleh Dinas Perdagangan Kabupaten Sukoharjo - Endah Andriyani; Purwono Sungkowo Raharjo; Rahayu Subekti (Jurnal Discretie, 2020)
This study aims to determine the implementation of supervision and law enforcement of minimarkets conducted by the Department of Commerce, Cooperatives, Small and Medium Enterprises Sukoharjo. This research is prescriptive normative legal research. This research uses primary and secondary legal material sources as well as data collection techniques using the legislative approach method. The data analysis technique in this study uses the syllogistic deduction method. This research shows that the supervision of minimarkets is carried out regularly and specifically. Periodic monitoring is carried out in accordance with plans that have been carried out. Supervision is specifically carried out when the Department of Trade, Cooperatives, Small and Medium Enterprises get a report from the public and related agencies. Law enforcement is carried out by giving verbal warnings, warning letters up to three times, until the closure of the business.